Material cultures in public engagement re-inventing public archaeology within museum collections - Christophilopoulou, Anastasia 19XX- (Oxbow Books, 2020)
The Material Cultures in Public Engagement' volume seeks to document and explore the significant change in the relationship of Museums with collections of the Ancient World and their audiences. The volume establishes a new approach to the study of public archaeology as a discipline and application within Museums, by bringing together the voices and experiences of museum professionals (curators, conservators and researchers) and public engagement professionals. Chapters in this volume present clear case-studies of the variety and diversity of public engagement projects conducted currently within European Museums and beyond. While the majority of case studies presented in the volume's chapters stem from European Museum programmes, plenty of reference is made on parallel strategies and successful public engagement programmes outside Europe (e.g. recently implemented projects by the Pointe-a-Calliere Museum, Montreal, the Dallas and Cleveland Museums of Art, or the Metropolitan Museum of Art, New York, to name but a few). Case studies within the volume provide important insights as to why public engagement programmes have developed in different ways between Europe and the Americas, as well as whether these differences may stem from different curatorial practices. Finally, a number of studies included in this volume point out that methodologies and practices of public engagement applied currently by Museums in or outside Europe, are rarely the subject of theoretical and methodological scrutiny, unlike other fields of study of the Ancient World or other social sciences. In summary, chapters within the book promise to contribute to the advancement of public engagement with the Ancient World, as well as to the advancement of public archaeology itself as a practice
Keywords: Öffentlichkeitsarbeit; Museumspädagogik; Archäologisches Museum; Museums and community; Archaeology / Social aspects; Aufsatzsammlung